Radiation dermatitis: A narrative review of the Indian perspective - Kaustav Talapatra; Pritanjali Singh; Isha Jaiswal; Sama Rais; Saket Pandey (Cancer Research, Statistics, and Treatment, 2020)
One of the common and visible symptoms of radiation toxicity is radiation-induced dermatitis, which varies in intensity from slight erythema to dry and moist desquamation, ulceration, and sometimes skin necrosis. Radiation depletes the basal cell layer of the skin and initiates a complex sequence of events, leading to dose-dependent acute or late sequelae. These skin reactions may cause irritation and pain, delay treatment, and also reduce the quality of life of the patient undergoing radiotherapy. It is also a subject of major concern for female patients undergoing radiotherapy for the treatment of head-and-neck and breast cancers. Despite the technological advancements achieved in planning and delivery in the field of radiotherapy, most patients still experience radiation dermatitis (RD) as a side effect of the treatment. The severity of RD depends on multiple patient- and treatment-related factors. Although severe RD is rare in the current practice of megavoltage radiotherapy, some occasions necessitate active intervention by a multidisciplinary group to manage both acute and late radiation effects over the epidermis and sometimes the dermis. Management policies vary as per the institutional guidelines and personal preferences and are mostly based on individual experiences and reviews. This is a narrative literature review of the various articles focusing on the diverse spectrum of RD. The primary search for the articles was carried out via Google Scholar, PubMed, and MEDLINE with keywords such as “radiation dermatitis,” “radiation-induced skin toxicity,” and “radiation recall phenomenon,” “radiation erythema,” and “radionecrosis.” Additional articles were found through references from the relevant articles. In this review, we discuss the incidence of RD, its presentation, the key aspects that put Indian patients at an increased risk of RD, and the management strategies for the prevention and treatment of radiation dermatitis.